1997
DOI: 10.1128/aem.63.9.3695-3697.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on distribution of Listeria ribotypes in corn, hay, and grass silage

Abstract: Listeria spp. isolated from 13 of 129 (10%) corn silage samples, 21 of 76 (28%) hay silage samples, and 3 of 5 (60%) grass silage samples during a previous Vermont survey were subjected to automated ribotype (RT) analysis. The 13 positive corn silage samples contained 3 Listeria monocytogenes isolates (three RTs, including one known clinical RT) and 10 L. innocua isolates (four RTs). Similarly, 2 L. monocytogenes isolates (two RTs) and 19 L. innocua isolates (three RTs) were identified in the 21 positive hay s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 15 publications
(16 reference statements)
2
26
1
Order By: Relevance
“…An antilisterial effect of enterolysin A, confirmed in this study, could contribute to the control of these pathogenic bacteria within the rumen ecosystem, where low‐quality silage is a main source of Listeria spp. (Ryser et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An antilisterial effect of enterolysin A, confirmed in this study, could contribute to the control of these pathogenic bacteria within the rumen ecosystem, where low‐quality silage is a main source of Listeria spp. (Ryser et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen is important to the survival and growth of this bacterium in silage (Fenlon 1986). The species L. monocytogenes, L. innocua, L. welshimeri, L. grayi, L. seeligeri and L. ivanovii have been identified in different types of silage (Ryser et al 1997;Santos et al 2013;Durmaz et al 2015;Nucera et al 2016) (Table 4). Listeria monocytogenes is the most worrisome and causes listeriosis, a type of feed-borne infection with a high mortality rate; clinical manifestations include encephalitis, abortion and septicaemia in several animals and humans (Duni ere et al 2013).…”
Section: Listeriamentioning
confidence: 99%
“…Many researchers have noted that the pH must be <4Á4 (Pauly 2009); however, research has shown Listeria sp. growth in silage in which the pH is close to or even below 4 (Ryser et al 1997;Abbas and Jaber 2010). Pauly and Tham (2003) and Fenlon (1989) evaluated the effects of various environmental factors, such as dry matter, water activity, acidification (pH) and fermentation products, on the growth of L. monocytogens.…”
Section: Listeriamentioning
confidence: 99%
“…Although the majority of bacteria associated with manures are beneficial and/or innocuous, the potential for the contamination of agricultural environments, livestock and crops with manure-borne pathogens necessitates greater knowledge of their persistence. Studies have shown that livestock water and feed sources serve as reservoirs for pathogenic organisms and as a vehicle for the transmission of pathogens through herds (Ryser et al 1997;Davis et al 2003;Johansson et al 2005;Wagner et al 2005;Cook et al 2010). As a result, there has been increased emphasis on understanding how manure-borne pathogens are spread between and within farms, focusing on contamination sources on the preharvest side of food production (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, persistence of other pathogens (Listeria monocytogenes (L. monocytogenes), Salm. enterica, enterococci and streptococci) in silage has been more variable (Ryser et al 1997;Mart ınez-Gamba et al 2001;Johansson et al 2005;Ram ırez et al 2005;Petersson-Wolfe et al 2011). In a study to determine routes of transmission of L. monocytogenes on dairy farms producing cheese from raw milk, Schoder et al (2011) found that the organism was three to seven times more likely to occur on farms where silage was fed than on those not feeding silage.…”
Section: Introductionmentioning
confidence: 99%